Improved methodology development for assessing the reservoir collector properties by the quantitative reservoir characterization tools - Martus, Olena; Petrash, Oleksandr (Technology audit and production reserves, 2022)
The object of research in the paper is the process of fluid transfer through the pore space of the reservoir rock. In this paper, using an expert method, the shortcomings of the Ukrainian methodology for assessing the reservoir properties of the reservoir were highlighted. In particular, the sources of uncertainty accumulation in determining the absolute values of the reservoir’s filtration parameters have been identified. The existing problem is that the algorithms of actions, which are the basis of the Ukrainian method of assessing reservoir properties, introduce a significant degree of uncertainty into the assessment results. In order to reduce uncertainty, the introduction of the concept of a representative elemental volume is considered when conducting laboratory research and the construction of a three-dimensional digital model of this elementary volume. It is suggested to improve the Ukrainian method of assessing the collector properties of the deposit based on current Western research. It was established that the standard methods of assessing the reservoir properties of the deposit are a source of accumulation of uncertainty in the development of technological documentation for the development of the deposit. The work is aimed at the development of an improved methodology for assessing the collector properties of the deposit. It is proposed to add to the action algorithm the stage of determining the representative volume of the sample, building its three-dimensional model, and digitizing it. At the final stage, the connectivity of the pores inside the sample is determined using the Minkowski function to improve the quality of the project documentation for the development of deposits. Guidelines have been developed to improve standard methods for assessing the collector properties of the deposit. The use of an improved methodology for assessing the reservoir properties of the deposit leads to a significantly lower degree of uncertainty and helps to form a more reliable picture of the operation of the reservoir at the design stage of its development. The presented study will be useful for the engineering personnel of foreign contractor companies, as it justifies the need to collect additional core material and sets the quality criteria of the information obtained about the collector properties of the deposit.